CYTOTYPES OF MUTANT DROSOPHILA MELANOGASTER STOCKS FROM THE COLLECTION OF THE GENETICS OF POPULATION LABORATORY OF THE INSTITUTE OF CYTOLOGY AND GENETICS SB RAS: GENOTYPES OF THE WOLBACHIA ENDOSYMBIONT AND HOST MITOTYPES - Yu. Yu. Ilinsky; R. A. Bykov; I. K. Zakharov (Вавиловский журнал генетики и селекции)
Wolbachia is a genus of maternally inherited bacteria that is widespread in field populations of Drosophila melanogaster. However, there are no sufficient data on Wolbachia infection among laboratory mutant stocks. We show the wide prevalence of Wolbachia among 353 mutant stocks from the collection of the Genetics of Populations Laboratory, Institute of Cytology and Genetics (ICG), Novosibirsk, Russia. The endosymbiont has been stably inherited in laboratory stocks for a long period of time. Two uninfected stocks from the collection are considered as a result of bacteria loss during maintaining them in the laboratory. There are three Wolbachia genotypes: wMel, wMelCS, and wMelCS2 in the collection. As endosymbiont is coinherited with mytochondria the definite cytotypes are formed from Wolbachia genotypes and mytotypes. We have revealed four cytotypes: M-MEL, M-w-, S-CS, and S-w– in the collection that had been described earlier for field populations of D. melanogaster. The cytotype and genotype frequency patterns differ significantly from those encountered in the wild, that is accounted for genealogy of each stock.